VIBRATION AND MODAL TRUSS GANTRY CRANE ANALYSIS USING ANSYS - Shah Akbar Siregar , Dionesta; Debi Puspa , Sofia; Soeharsono, Soeharsono; Sukarnoto, Tono; Adinegoro , Faisal (Metrik Serial Teknologi dan Sains, 2025)
Cranes are indispensable heavy equipment that can lift and move hefty loads in factories, warehouses, and construction sites with ease. Safe operation of cranes is vital because errors in crane design can make it prone to failures, such as broken trusses, which can cause the crane to collapse and hit people around the crane. This research aims to analyze vibrations and modal Truss Gantry Cranes using ANSYS software to determine natural frequencies, critical points, and deformations that can result in damage. To test the Truss Gantry Crane's structural strength with ANSYS software, the Static Structural design program is used to analyze the deformations and stresses experienced by the crane, the Modal design program is utilized to determine its natural frequency, and the Harmonic Response is used to determine its reaction to natural frequencies. Static Structural testing was carried out 30 times, starting from a load of 500 N and increasing to a maximum load of 15000 N, with an interval of 500 N. The test results showed that the Truss Gantry Crane vibrates violently at frequencies of 24 Hz, 68 Hz, and 94 Hz. Further analysis revealed a linear regression analysis for the maximum load and maximum stress that can be applied to the Truss Gantry Crane as follows: y = 0,0091 x + 0,1981